2014
DOI: 10.1007/s00221-014-3946-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Protective effects of melatonin against mitochondrial injury in a mouse model of multiple sclerosis

Abstract: Multiple sclerosis (MS) is the most prevalent inflammatory demyelinating disease of the central nervous system. Besides other pathophysiological mechanisms, mitochondrial injury is crucially involved in the development and progression of this disease. Mitochondria have been identified as targets for the peptide hormone melatonin. In the present study, we sought to evaluate the impact of oxidative stress on mitochondrial density and enzyme transcription during experimentally induced demyelination and the protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 49 publications
3
31
0
1
Order By: Relevance
“…Melatonin abolishes destructive cuprizone effects in the corpus callosum by decreasing oxidative stress, restoring mitochondrial respiratory enzyme activity and fusion and fission processes as well as decreasing intra-axonal mitochondria accumulation. Protective effects of melatonin against mitochondrial injury in a mouse model of MS were observed [63]. Bahamonde et al showed on the group of 18 MS patients that natalizumab significantly increases melatonin concentration and reduces oxidative stress biomarkers in perpherial blood [64].…”
Section: Multiple Sclerosismentioning
confidence: 96%
See 1 more Smart Citation
“…Melatonin abolishes destructive cuprizone effects in the corpus callosum by decreasing oxidative stress, restoring mitochondrial respiratory enzyme activity and fusion and fission processes as well as decreasing intra-axonal mitochondria accumulation. Protective effects of melatonin against mitochondrial injury in a mouse model of MS were observed [63]. Bahamonde et al showed on the group of 18 MS patients that natalizumab significantly increases melatonin concentration and reduces oxidative stress biomarkers in perpherial blood [64].…”
Section: Multiple Sclerosismentioning
confidence: 96%
“…Axonal loss is the main reason of disability progression in MS [59][60][61]. Patients with secondary progressive multiple sclerosis (SPMS) had lower activity of SOD [62,63]. Recent studies pointed out that melatonin genes pathway seems to be involved in MS progression.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…The level of oxidative stress-related markers of mitochondrial apoptosis (Bax, cleaved caspase-3, and PARP, cytochrome c release into the cytosol) decreased in the presence of melatonin in acute respiratory distress syndrome (Sun et al, 2015). Melatonin abolished destructive demyelination effects induced by the drug cuprizone in the corpus callosum, by decreasing oxidative stress and by restoring mitochondrial respiratory enzyme activity and fusion and fission processes (Kashani et al, 2014). Melatonin administration also reduced Bax translocation to the mitochondria and the release of cytochrome c into the cytosol, preventing brain injury following a subarachnoid hemorrhage (Chen et al, 2014).…”
Section: Melatonin and Mitochondriamentioning
confidence: 99%
“…Some studies have shown that cancer patients have a reduced fertility potential even before starting treatment (17)(18)(19)(20). For this kind of infertility, some reasons have been proposed: primary or secondary hormonal imbalance; anatomic changes (retrograde ejaculation); damage to supporting cells or germinal stem cells; reduction of sperm DNA integrity, numbers, and mo-tility; and a decrease in pituitary gonadotropin levels, all of which can negatively affect fertility (11,12,21,22).…”
Section: Introductionmentioning
confidence: 99%